2016
DOI: 10.1007/s10856-016-5765-7
|View full text |Cite
|
Sign up to set email alerts
|

Pure titanium particle loaded nanocomposites: study on the polymer/filler interface and hMSC biocompatibility

Abstract: The integration of inorganic nanoparticles into polymer matrices allows for the modification of physical properties as well as the implementation of new features for unexplored application fields. Here, we propose the study of a new metal/polymer nanocomposite fabricated by dispersing pure Ti nanoparticles into a poly(methylmetacrilate) matrix via solvent casting process, to investigate its potential use as new biomaterial for biomedical applications. We demonstrated that Ti nanoparticles embedded in the poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Both decomposition temperatures seem not to be affected by the increase of Ti concentration in contrast to some reported catalytic activity that accelerates decomposition. 26 Figure 5 summarizes these findings, where the residual mass (Figure 5(a)) and first derivative (Figure 5(b)) are plotted against temperature. The maximum temperature used during TGA was 650°C, which is far from the T m of titanium reported at 1668°C.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Both decomposition temperatures seem not to be affected by the increase of Ti concentration in contrast to some reported catalytic activity that accelerates decomposition. 26 Figure 5 summarizes these findings, where the residual mass (Figure 5(a)) and first derivative (Figure 5(b)) are plotted against temperature. The maximum temperature used during TGA was 650°C, which is far from the T m of titanium reported at 1668°C.…”
Section: Resultsmentioning
confidence: 77%
“…For pristine titanium only adsorbed water (3432 cm −1 ), carbon-containing species (2921 and 2852 cm −1 ), and oxidized titanium (705 cm −1 ) were observed. 26…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results implied that nTiO 2 could promote the proliferation of MG63 cells. It could be concluded that nTiO 2 was in favour of cellular proliferation and attachment, which might be due to the favourable biocompatility of nTiO 2 [47]. Further, the scaffolds with nTiO 2 were more hydrophilic, which could promote the interaction between cells and scaffolds [48,49].…”
Section: Resultsmentioning
confidence: 99%